Sengketa Kandidat Calon Perseorangan dalam Pemilihan Umum Bupati dan Wakil Bupati Ketapang Tahun 2020 di Tingkat Kabupaten Masa Perbaikan (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This article examines and discusses the Supreme Court judge's decision regarding the results of the Individual Candidate Dispute in the 2020 Ketapang Regent and Deputy Regent General Election at the Regency Level during the Improvement Period. viewed from the perspective of State Administrative Law. seen from the case and the way the judge assesses the case and the judge's decision. In this article we use qualitative research methods, which focus on observation and in-depth research. pay attention to human behavior and what aspects influence it. This is realized by looking at what aspects make the plaintiff object and what aspects influence the judge to make a decision